Wychowawcze oddziaływanie bohatera literackiego na młodzież w okresie dorastania = The Educational Influence of a Literary Hero on Young People During Adolescence - Dudzikowa, Maria (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article's object are contemplations on the conditions of influence of a literary hero an young people durring adolescence. Young people's evolution and social conditions bring about, that their attitude towards a literary hero bases on other lines tham the attitude of younger readers.
Keywords: bohater literacki; młodzież; wychowanie